Systemic autoimmune diseases presenting as acute myocarditis in pediatric emergency: Two case reports - Sayantan Mondal; Rituparna Das; Moumita Samanta; Madhumita Nandi (Wolters Kluwer Medknow Publications, 2021)
Children seldom present to the emergency with cardiac manifestations, some of which eventually are diagnosed as manifestations of rheumatological diseases such as systemic lupus erythematosus or arthropathies. While cardiac involvement is known in these cases, their presentation solely as a cardiologic event initially is not widely known. The following two case reports depict how cardiological emergencies ultimately evolve as systemic autoimmune diseases with atypical involvement such as myocarditis with heart failure and are salvaged with appropriate management.